Bilateral hip stability variation in the functional ambulation and kinetic parameters after total hip arthroplasty during leveled walking - Abd-Eltawab, Amany E.; Elsherbini, Dalia Mahmoud Abdelmonem; El Nashar, Eman Mohamad; Alshehri, Shaker Hassan; Alhefzi, Ali; Eldesoqui, Mamdouh; El-Sherbiny, Mohamed (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives This study determines gender variation, comparing the significance level between men and women related to functional ambulation characteristics after hip arthroplasty. The study focuses on the broader female pelvis and how it affects the rehabilitation regimen following total hip arthroplasty. Materials and Methods In this cross-sectional study, 20 cases of right hip arthroplasty were divided into 10 male and 10 female cases, aged 40–65 years. The functional ambulation parameters (walking cadence, gait speed, stride length, and gait cycle time) were acquired from the GAITRite device, as well as kinematic values for hip frontal plane displacement and kinetic parameters for ground response force in the medial–lateral direction. Results An independent t-test showed a significant difference in the kinematic parameter variables for the anterior superior iliac spine, more significant trochanter displacement, and hip abduction angle between the operated and non-operated limbs for each group separately. Regarding the functional ambulation parameters, there was a significant difference in the walking cadence between the operated and non-operated limbs of both male and female groups. Moreover, the output variables of ground reaction force measures revealed significant differences between their operated and non-operated limbs. The linear regression model used was consistent with the current results, demonstrating a weak negative correlation between the abduction angle of the operated hip and gait speed for both male and female groups. Conclusion Based on the findings, we draw the conclusion that improving a rehabilitated physical therapy program for the abductors of both male and female patients’ operated and non-operated limbs is essential for normalizing the ground reaction force value, avoiding focus on the operated hip, and reducing the amount of time that the operated hip’s abductors must perform. This involves exposing the surgically repaired limb to the risk of post-operative displacement or dislocation, particularly in female patients.